ANALYSIS OF SUPPLY COMPONENT OF BETA VALVE, BLEED VALVE AND PROPELLER REDUCTION GEARBOX - Ririn Isnawati (Institut Teknologi Dirgantara Adisutjipto, 2020)
Maintenance is a very important thing to do in order to keep the aircraft in flightworthiness. One form of maintenance activity is the replacement of components that have been damaged (failed). Inventory components can not be a avided because to get it can not be done suddenly while for those needs can occur suddenly. Thus, it is necessary to plan the number of component inventories so that smooth production is maintained. Efforts to solve these problems use the Mean Time Between Removal (MTBR) equation. Where MTBR is used to determine inventory levels and component replacement scheduling. In addition, the MTBR is a formula or model to determine how much inventory per year will minimize the depletion of inventory in the depository and for estimating component replacement. From the data processingof the G120 TP-A GROB, the number of component inventories in one year is based on the age of components from manufacture (MTBRStandard), among others: 10 Beta Valve Components, 17 Bleed Valve Components, and 13 Propeller Reduction Gearbox Components